Model Development for Measuring and Analyzing Green Accounting Activities Using Factor Analysis - Lisa Kartikasari; Dian Essa Nugrahini (Jurnal Akuntansi Indonesia, 2025)
One of Corporate social responsibilities to the environment is by disclosing environmental information as a result of industrial activities or their business. It covers a clear figure of a company to combine cost and environmental benefits in economic decision making reflected in the implementation of green accounting. The purpose of this study is to establish indicators and constructs of green accounting activities by identifying environmental activities grouped into the green support, appraisal, internal failure activities, external failure activities and hidden activities. The population in this research is manufacturing companies in the Central Java province which is administered by purposive sampling technique. It is obtained a sample of 43 companies. Then, the data are analyzed by using factor analysis in order to establish and construct appropriate indicators for green accounting.The findings show that 21 selected indicators with five constructs of green accounting activities. Five constructs with the respective variables as follows: green support activities with six indicators, green appraisal activities with four indicators, green internal failure activities with five indicators, green external failure activities with three indicators and green hidden constructs activities with three indicators.